Structure determination of superatom metallic clusters using rapid scanning electron diffraction - Bruma, Alina (2016)
Experimental analysis of electron diffraction patterns for ligand-stabilized gold clusters in transmission electron microscopy is a cumbersome procedure, due to electron beam–induced irradiation damage. We propose herein a method for instantaneous data collection using scanning nanobeam electron diffraction and the subsequent determination of the crystal metallic clusters. The procedure has been tested on a known structure, namely Au102(p-MBA)44 nanoclusters and has been compared with their structure theoretically determined by ones previously obtained from X-ray diffraction analysis. The method can be unambiguously applied for the case of any nanoscale system susceptible to electron beam damage and it is capable to register the rotation effect on the metallic clusters caused due to the electron beam interaction during the raster scanning on the sample.